Analysis Of Spatial Pattern Of Distribution Of Post-Vaccination Covid-19 Cases in Bombana District - wulandari, pradea (Jurnal Sistem Informasi Kesehatan Masyarakat, 2023)
Background: At the end of 2019 a pandemic emerged, namely the 2019 coronavirus disease (COVID-19). Technology in mapping Covid-19 cases is very important. Currently, there are many and there are already mappings for Covid-19 cases carried out by the government, for example, the mapping carried out by the COVID-19 website.go.id. Bombana Regency is divided into two parts or two islands which have quite difficult access to health facilities. Roads that are difficult to access will be an obstacle for the surrounding community when they want to go to health facilities and want to vaccinate. This study aims to see the pattern of distribution of post-vaccination COVID-19 cases in Bombana RegencyMethods: This research was conducted in Bombana Regency, Southeast Sulawesi. This study uses secondary data for COVID-19 in 2020 and 2021 and vaccination data for 2021 in Bombana district. This type of quantitative descriptive research uses autocorrelation spatial analysis method (Moran's I).Results: The results of the Moran's I autocorrelation analysis obtained a Morans index value of 0.228974 while the p-value was 0.007430 and the z-score was 2.676938, which means that the spatial pattern of COVID-19 cases based on population density is clustered. Moran's I autocorrelation analysis results obtained a Morans index value of 0.285945, while the p-value was 0.006556 and the z-score was 2.718601, which means that the spatial pattern of COVID-19 cases in 2020 is clustered. The results of the Moran's I autocorrelation analysis showed that the Morans index value was 0.104219 while the p-value was 0.169993 and the z-score was 1.372227, which means that the spatial pattern of COVID-19 cases after vaccination in 2021 is random or spread.Conclusion: The pattern of distribution of COVID-19 cases based on population density using Morans'I autocorrelation spatial analysis forms a clustered pattern. The distribution pattern of COVID-19 cases in 2020 using Morans'I autocorrelation spatial analysis forms a clustered pattern. The distribution pattern of COVID-19 cases in 2021 using Morans'I autocorrelation spatial analysis forms a spreading pattern. Dissemination is done by suggesting a dashboard display for the Bombana district government website